Limitations of reproductive rights: Certain general theoretic aspects - Sviatoslav Dobryanskiy (Wrocławsko-Lwowskie Zeszyty Prawnicze)
As is well known of the most sharp problems of the theory and practice of fundamental rights and freedoms legal safeguarding is the question of human rights limitations of such rights. Namely, discursive and not sufficiently researched remains the problem of legal regulation of reproductive rights limitations both in international, and in national legislation on these items.